Mechanism of Tunable Band Gap of Halide Cubic Perovskite CsPbBr3−xIx - Veysel Çelik (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Perovskites are organic-inorganic compounds with a crystal structure that revolutionize many optoelectronic applications, especially solar cells. The CsPbBr3−xIx, a perovskite, has garnered significant attention due to its tunable band gap and excellent photovoltaic properties. In this theoretical study, the structural, electronic, and optical properties of CsPbBr3−xIx are investigated through density functional theory calculations. The calculations reveal that the substitution of Br with I leads to a significant reduction in the band gap of CsPbBr3−xIx, resulting in improved light absorption properties. The obtained data show that the coexistence of Br and I ions in the structure creates an energy level similar to the shallow energy levels caused by doping at the R symmetry point in the band structure.